2017
DOI: 10.17770/sie2017vol1.2400
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Professional Competence of Students Future Teachers of Vocational Training in the System of Higher Education on Kazakhstan

Abstract: AnotācijaMeruyert Zhanguzhinovas promocijas darbs"Studentu -topošo profesionālās izgl t bas pedagogu profesionālās kompetences veidošanās Kazahstānas augstākajā izgl t bā" izstrādāts Rēzeknes Tehnoloģiju akadēmijaā Dr. paed. profesores Velta ubkina vad bā.Pēt juma objekts: studentu -topošo profesionālās izgl t bas pedagogu profesionālās kompetences veidošana.Pēt juma priekšmets: studentu -topošo pedagogu profesionālās kompetences veidošanās likumsakar bas un dinamiskās saites.Pēt juma mērķis: noskaidrot profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The research of the problems of professional preparation of teachers on the base of international experience revealed two directions in Formation of Professional competence (FPC) on "methodic" and on the "system" (Zhanguzhinova, 2017), what allowed to determine: Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of the problems of professional preparation of teachers on the base of international experience revealed two directions in Formation of Professional competence (FPC) on "methodic" and on the "system" (Zhanguzhinova, 2017), what allowed to determine: Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhanguzhinova, another key factor as a system-based direction in the modernization of the system of training is an advantage of the credit system in higher educational institutions of Kazakhstan: the formation of modular educational programs, promotion of Academic Mobility opportunities, ECTS, strengthening of scientific and research activity of students, because the root of the problem is inadequate training of specialists of the educational springboard (Zhanguzhinova, 2017).…”
Section: Objectives Of the Projectmentioning
confidence: 99%
“…1. The active teaching methods that contributed to the formation of: − pedagogical interaction (students, teachers, employers); − value attitudes and interest in the profession, stimulating, communicative, heuristic, cognitive knowledge, skills, attitudes of students; − statistical, conceptual generalization, statement of facts and learning outcomes of students based on the Methodology; − for the formation of: systemic, statistical, rational, predictive knowledge, skills, attitudes of students; − manifested in the forms of work: presentation, fashion show, performance, defile, exhibiting, demonstration, exam, control task, final / midterm control, verification, questioning, testing, certification, monitoring (Zhanguzhinova, 2018). The identified methods of organizing the pedagogical process are reflected in Table 1: On the basis of the identified methods, below are the forms of organizing the pedagogical process in educational programs of Scenography.…”
Section: Activation Of Problematic Teaching Methods In Educational Programs Of Scenographymentioning
confidence: 99%
“…The research revealed the methods and forms in the organization of the pedagogical process of the Department of Scenography (Zhanguzhinova, 2018) (see Table 2…”
Section: Educational Forms Of the Organization Of Pedagogical Process For Scenography' Educational Programsmentioning
confidence: 99%
“…There were special yurts for kitchens and warehouses. During the campaigns of Genghis Khan, there were yurts on wheelskind of the ancestors of the current trailers [15].…”
Section: Fig 3 Perfect Air Circulation Through Lattice Walls Creatimentioning
confidence: 99%